THE PRACTICAL IN THEORY AND THE THEORETICAL IN PRACTICE: FACILITATING INTEGRATION IN TEACHING AND LEARNING - Van Rensburg, Viki (Journal of Community and Health Sciences, 2020)
Introduction: The integration of theory and practice in student learning is a challenge faced by teachers in health science education, where the curriculum contains large sections of learning in clinical or fieldwork settings. Theoretical modules traditionally precede fieldwork modules with the assumption that theory prepares students for fieldwork. However, students report lack of confidence and struggle to integrate theory and practice. The findings of an action research study of the facilitation of theory-practice integration in health sciences education is reported in this paper. Objectives: The objective of the study was to investigate the creation of learning opportunities that would result in improved confidence in clinical decision-making in fieldwork. Methods: A qualitative approach with an action research strategy was used to execute the research. Results: Using reflective diaries and real life problems can enhance the integration of theory and practice. Participants: Third year occupational therapy students. Setting: University of the Western Cape, community and school based facilities. Intervention: Implementation of additional learning opportunities to integrate theory and practice. Conclusion: Introducing alternative learning strategies to integrate theory and practice can improve the learning outcomes of students who follow professional degrees.